2014
DOI: 10.1115/1.4028462
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hydrogen Enriched Natural Gas Flames in a SGT-700/800 Burner Using OH PLIF and Chemiluminescence Imaging

Abstract: The effect o f hydrogen enrichment to natural gas flames was experimentally investigated at atmospheric pressure conditions using flame chemiluminescence imaging, planar laser-induced fluorescence of hydroxyl radicals (OH PLIF), and dynamic pressure moni toring. The experiments were petformed using a third generation dry low emission (DLE) burner used in both SGT-700 and SGT-800 industrial gas turbines from Siemens. The burner was mounted in an atmospheric combustion test rig at Siemens with optical access in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Similar observations were reported by Park and Lee [70] and Kim et al [71] in later investigations using the same burner. The excitation of higher frequency instabilities due to hydrogen enrichment has also been reported in other studies [64,72,73].…”
Section: Effect On Stability Maps and Dynamic State Transitionssupporting
confidence: 78%
See 3 more Smart Citations
“…Similar observations were reported by Park and Lee [70] and Kim et al [71] in later investigations using the same burner. The excitation of higher frequency instabilities due to hydrogen enrichment has also been reported in other studies [64,72,73].…”
Section: Effect On Stability Maps and Dynamic State Transitionssupporting
confidence: 78%
“…On the contrary, the work of Lantz et al [72] revealed that transition to an M-shaped flame due to hydrogen enrichment in their combustor coincided with a suppression of self-excited combustion instabilities. The authors investigated natural gas flames enriched with up to 80% hydrogen by volume at atmospheric pressure using a third generation dry low emissions (DLE) burner employed by Siemens Energy in their SGT-700 and SGT-800 industrial gas turbines.…”
Section: Effect On Flame Structure and Flame Positionmentioning
confidence: 91%
See 2 more Smart Citations
“…26,27 Therefore, OH has been frequently used for tracing the position of the flame front by tracking steep gradients in the OH-planar laser-induced fluorescence (PLIF) image data. [28][29][30] Another approach to track the flame front region is to visualize CH or HCO, which are intermediate combustion species that form and be consumed in this thin layer. [31][32][33][34][35] The region where the preheating chemistry occurs, i.e., before the actual flame front, can be visualized by performing PLIF on formaldehyde, CH 2 O.…”
Section: Laser-induced Fluorescencementioning
confidence: 99%